Taxonomic revision of the Celtis iguanaea complex (Cannabaceae) - Zamengo, Henrique Borges; Chamorro, Débora C.; Houtepen, Erik A.t.; Gaglioti, André Luiz; Pederneiras, Leandro Cardoso; Prado, Darién E.; Oakley, Luis J. (Phytotaxa, 2025)
Morphological studies on Celtis over the last 50 years shown that pyrenes contain specific characters useful for the delimitation of its species. Taxonomic revisions of groups in this genus, however, ignored the pyrenes, leading to the recognition of highly variable species complexes. In this study, we reexamine one of such groups, the C. iguanaea species complex, to evaluate its taxonomy. This taxonomic group is widely distributed in the Neotropical region and was previously treated as a single species. Numerous species-level synonyms have been used. No modern taxonomic and nomenclatural revision has been available. To correctly delimit C. iguanaea s.str. and the other species accepted here, we reviewed all published records and selected herbarium specimens (including types). The main results include (1) a modified taxonomic concept, (2) a revision of the taxonomy, nomenclature, and synonymy (with new or corrected typifications), (3) a revision of distribution ranges, (4) designation of lectotypes for C. anfractuosa, C. aculeata var. pubescens, C. aculeata var. serrata, C. punctata, C. zizyphoides and Ziziphus commutata, (5) correction of lectotype designation of C. iguanaea, and (6) designation of epitypes for C. iguanaea and C. tarijensis. In addition, we propose the new combination Celtis tarijensis (≡Momisia tarijensis) and included Celtis punctata (≡Sarcomphalus punctatus) in the synonymy of C. iguanaea. Finally, we provide an identification key that distinguishes C. iguanaea s.str. from all related species.